Alas Kaki Yang Tepat Menurunkan Risiko Luka Kaki Diabetik; Literature Review - Siska Misali; Saldy Yusuf; Yuliana Syam (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: to identify the right type of footwear in reducing the risk of Diabetic Foot Ulcer (DFU).Methods: Literatures was sourced from database PubMed, Wiley, Springer and Google scholar, published from 2015 to 2019, and manually select the relevant article or in accordance with the research question. Results: DFU is more commonly found in areas that are in contact with footwear. Sandals are the footwear that is more widely used in daily life. Modified footwear can reduce plantar pressure.Conclusion: Appropriate footwear is recommended for DM sufferers because it can reduce plantar pressure which is a supporting factor for DFU.